Effects of Extinction on Classical Conditioning and Conditioning-Specific Reflex Modification of Rabbit Heart Rate - Burhans, Lauren B. (2009)
Understanding the mechanisms of fear extinction has become increasingly important for treating a number of disorders, particularly post-traumatic stress disorder. Conditioning of rabbit heart rate (HR) is an established model for studying fear, yet little is known about procedures for extinguishing it other than repeated presentations of cue(s) associated with the fear-inducing event. The following study examined the effects of conditioned stimulus (CS) alone, unconditioned stimulus (US) alone, unpaired CS/US presentations, continued CS-US pairings, or no further stimulation on rabbit HR following HR conditioning. We have previously shown the rabbit HR response to the US can change as a function of learning when measured in the absence of the CS, a phenomenon referred to as conditioning-specific reflex modification (CRM). More specifically, the HR exhibits a deceleration in response to the US reminiscent of the conditioned bradycardia that develops to the CS. Consequently, the following study also examined the effects of extinction treatments on HR CRM. For HR conditioned responses (CRs), CS-alone and unpaired CS/US presentations were the most successful extinction treatments. For HR CRM, all conditions led to a reduction in CRM except for a subset of rabbits that maintained high levels following unpaired extinction, indicating a dissociation between extinction of HR CRs and CRM. The findings highlight the parameters of HR extinction, the transient nature of HR CRM, vagal involvement in both acquisition and extinction of HR CRM, and suggest that HR CRM cannot be fully explained as a CR that has generalized from the CS to the US.